“BASENGAJA” APPROACH - AN APPROACH OF TEACHING BASIC PROGRAMMING - Victor N. Papilaya (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2011)
“Basengaja” approach is an approach of teaching basic programming. This approach is designed to help the students who faced problems in following the lecture of basic programming. The basic idea of this approach is to reverse the sequences of regular teaching approach with two additional steps. The purpose is that in the such as mechanism the students will firstly learn the basic logic of thinking in programming instead of the complexity of language programming commands itself. Furthermore, this approach needs the simple IDE that can be used to simplify learning process. With this IDE, the students are not required to remember or to know commands of language programming to solve certain problem. For this reason, an IDE called Oledit is developed. Based on the direct observation and the profile of the students after learned basic programming using this approach, the result shows that this approach brings the positive contribution.